Proceedings of the 13th International Conference on Human Computer Interaction With Mobile Devices and Services 2011
DOI: 10.1145/2037373.2037397
|View full text |Cite
|
Sign up to set email alerts
|

The effects of walking, feedback and control method on pressure-based interaction

Abstract: This paper presents a study looking into the effects of walking and the use of visual and audio feedback on the application of pressure for linear targeting. Positional and Ratebased control methods are compared in order to determine which allows for more stable and accurate selections, both while sitting and mobile. Results suggest that Rate-based control is superior for both mobile (walking) and static (sitting) linear targeting, and that mobility significantly increases errors, selection time and subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
(33 reference statements)
1
30
0
Order By: Relevance
“…Therefore, our direction control modalities were Touch and Dial. A pressure sensor was chosen for one of the speed control modalities, since pressure has been demonstrated to be a useful modality for the control of speed (for rate based cursor control) [16]. A pressure sensor can be mapped well to the control of speed using an accelerator metaphor, where increasing the force will increase the speed and vice versa.…”
Section: Input Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our direction control modalities were Touch and Dial. A pressure sensor was chosen for one of the speed control modalities, since pressure has been demonstrated to be a useful modality for the control of speed (for rate based cursor control) [16]. A pressure sensor can be mapped well to the control of speed using an accelerator metaphor, where increasing the force will increase the speed and vice versa.…”
Section: Input Methodsmentioning
confidence: 99%
“…A pressure sensor can be mapped well to the control of speed using an accelerator metaphor, where increasing the force will increase the speed and vice versa. Furthermore, isometric force input is useful as an input modality on mobile devices [16][17][18] and as an augmentation of finger/stylus input on touchscreens [19] (although not tested in the NDH). It can be detected using force sensing resistors (FSRs) that are flat and can be added to different locations on a device without changing its form factor.…”
Section: Input Methodsmentioning
confidence: 99%
“…Another example is the tablet prototype presented in [22]: a pressure sensor is attached to the front bezel held with the dominant hand. As most previous work that investigated pressure as an input channel [20,24], they considered a single pressure sensor, which limits the range of tasks users can achieve with it.…”
Section: Background and Motivationmentioning
confidence: 99%
“…These were connected to SAMH Engineering SK7-ExtGPIO01 I/O modules for analogue-to-digital conversion and sensor output linearization [2]. The two I/O modules were then connected to a MacBook Pro via USB for signal processing, which forwarded the sensor output over USB to an HTC Nexus One Android mobile phone (see Figure 1, left) to present the application GUI.…”
Section: Experimental Designmentioning
confidence: 99%
“…It can add a 3 rd dimension to typically 2D touch interfaces as well as continuous and real-time control over content such as zooming, scrolling, panning or rotation. Research has shown pressure input on mobile devices to be highly precise when the user is sitting and walking, even using only audio feedback [1,2]. However most research has only used a single finger for interaction, or a single point of pressure.…”
mentioning
confidence: 99%